The interaction of lncRNA EZR-AS1 with SMYD3 maintains overexpression of EZR in ESCC cells. Issue 4 (14th December 2017) - Zhang, Xiao-Dan; Huang, Guo-Wei; Xie, Ying-Hua; He, Jian-Zhong; Guo, Jin-Cheng; Xu, Xiu-E; Liao, Lian-Di; Xie, Yang-Min; Song, Yong-Mei; Li, En-Min; Xu, Li-Yan
Abstract: EZR, a member of the ezrin-radixin-moesin (ERM) family, is involved in multiple aspects of cell migration and cancer. SMYD3, a histone H3–lysine 4 (H3–K4)-specific methyltransferase, regulates EZR gene transcription, but the molecular mechanisms of epigenetic regulation remain ill-defined. Here, we show that antisense lncRNA EZR-AS1 was positively correlated with EZR expression in both human esophageal squamous cell carcinoma (ESCC) tissues and cell lines. Both in vivo and in vitro studies revealed that EZR-AS1 promoted cell migration through up-regulation of EZR expression. Mechanistically, antisense lncRNA EZR-AS1 formed a complex with RNA polymerase II to activate the transcription of EZR. Moreover, EZR-AS1 could recruit SMYD3 to a binding site, present in a GC-rich region downstream of the EZR promoter, causing the binding of SMYD3 and local enrichment of H3K4me3. Finally, the interaction of EZR-AS1 with SMYD3 further enhanced EZR transcription and expression. Our findings suggest that antisense lncRNA EZR-AS1, as a member of an RNA polymerase complex and through enhanced SMYD3-dependent H3K4 methylation, plays an important role in enhancing transcription of the EZR gene to promote the mobility and invasiveness of human cancer cells.